إعداد خطة حماية من انخفاض تردد وجهود نظام القدرة الكهربائي تعتمد على الفصل المناسب للأحمال - حجار عمار; ساعاتي محمد; محجازي ياسمين (Latakia University Journal -Engineering Sciences Series, 2018)
The imbalance in generation/load in the electrical power systems causes a decrease in both frequency and voltage profile. BothFrequency and voltagesdeviationare usually allowed in predefined values, so that the power system is not subject to partial or total blackout. This paper introducesa protection scheme for the electrical power system, to protect against under frequencyunder Buses voltage which based on the suitable load shedding. The introduced scheme uses the rate of frequency change as an instantaneous indicateto detect case of imbalance generation/load with considering into the account the magnitude of the disturbance, reactive power demand and the priority of loads. The introduced scheme has the ability to properly determine the load to be shed, in order to restore frequency and voltages of the power system quickly and avoiding the occurrence of partial or total blackout of the system. To evaluate the performance of the introduced protection scheme for a typical test power system, (IEEE-14 bus test system), is modeled by using(ETAP: Electrical Transient and Analysis Program) platform, many cases of disturbance are simulated on it(outage of generator/ transmission line of the service, 3phase fault, and over load), then the introduced scheme is implemented and both frequency and voltage are observed before and after load shedding. The simulation results showed of the introduced schemeperforms high speed and efficiency manner in suitable load sheddingfor all tested cases. تتعرّض أنظمة القدرة الكهربائية إلى حالات انخفاض في التردد والجهود نتيجة لعدم التوازن بين التوليد والحمل. لايُسمح عادة بانحراف التردد والجهود عن قيم محددة مسبقاً، وذلك كي لايتعرض نظام القدرة الكهربائي إلى خطر التعتيم الجزئي أو الكلي. يقدم هذا البحث خطة حماية لنظام القدرة الكهربائي مخصصة للحماية من انخفاض التردد والجهود تعتمد على الفصل المناسب للأحمال. تستخدم هذه الخطة معدل التغيّر في التردد كمؤشر فوري لاكتشاف حالة عدم التوازن بين التوليد والحمل، مع الأخذ بالحسبان حجم الاضطراب،والطلب على الاستطاعة الردية، وأهمية الأحمال. تمتلك الخطة المقدمة المقدرة على التحديد المناسب لمقدار الحمل اللازم فصله، وذلك لاستعادة تردد وجهود النظام بسرعة وبالتالي لتجنب حدوث التعتيم الجزئي أو الكلي. لاختبار أداء خطة الحماية المقدّمة تمّ نمذجة نظام قدرة اختباري نموذجي(IEEE-14bus test system) باستخدام برنامج محلل الحالات العابرة الكهربائية (ETAP: Electrical Transient Analyzer Program)، وتمّ محاكاة مجموعة من الاضطرابات عليه (خروج موّلد / خط نقل عن الخدمة، عطل ثلاثي الطور، تحميل زائد)، ثمّ تم تطبيق الخطة المقدمة ومراقبة التردد والجهود قبل وبعد فصل الأحمال. لقد أثبتت نتائج الاختبارات فعالية الخطة المقدمة من حيث الدقة والسرعة في الفصل المناسب للأحمال لأجل جميع الحالات المختبرة.